Forecasting and evaluation for transportation planning - American Institute of Certified Planners (Chicago : American Institute of Certified Planners, 1994)
How do you avoid "black box" mysteriesn Jim Gosnell explores the information foundation and evaluative systems of transportation planning. He examines the complexity, constraints, uncertainty, and methods involved in determining what information is important. This is a practical discussion of how to address decision and information needs for good transportation planning.
VHS
Keywords: Transportation -- Planning -- Evaluation